2021
DOI: 10.1177/1420326x211017175
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations and the influence of ventilation rates on IAQ: A case study of five low-energy London apartments

Abstract: The indoor air quality (IAQ) of five low-energy London apartments has been assessed through the measurement of 16 key pollutants, using continuous and diffusive methods across heating and non-heating seasons. This case study approach aimed to assess the presence of pollutants within low-energy apartments and to better understand the role of ventilation and seasonal variations in indoor air quality. The results indicate strong seasonal variations, driven by increased natural ventilation rates over the summer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In contrast, they revealed significantly higher levels in the winter months, with concentrations peaking at 15.3 µg/m 3 for the corridor and 17.6 µg/m 3 for the bathroom. The consistent findings extend to environmental monitoring in English homes, revealing a notable trend of formaldehyde concentrations decreasing by half from winter to summer [59]. The variation in trends between the office and other rooms may be attributed to disparities in ventilation systems.…”
Section: Resultssupporting
confidence: 74%
“…In contrast, they revealed significantly higher levels in the winter months, with concentrations peaking at 15.3 µg/m 3 for the corridor and 17.6 µg/m 3 for the bathroom. The consistent findings extend to environmental monitoring in English homes, revealing a notable trend of formaldehyde concentrations decreasing by half from winter to summer [59]. The variation in trends between the office and other rooms may be attributed to disparities in ventilation systems.…”
Section: Resultssupporting
confidence: 74%
“…Both Chamseddine et al ( 2019 ) and Zaman et al ( 2021 ) offered possible explanations for these seasonal variations; both cited that increased indoor activity during the cold season increased the rate of pollutants influx, ultimately causing the observed surges in concentrations. It should be noted that the impact of seasonality on indoor air quality is not limited to the hospital setting; several studies have reported similar observations for residential settings (Abdel-Salam 2021 ) and in learning institutions (Deng and Lau 2019 ; Stamp et al 2022 ). In comparison, the spatial variability of microorganism levels in hospitals remains less studied.…”
Section: Introductionmentioning
confidence: 81%
“…Apart from the comfort, air velocity could also affect the indoor air quality. 1,51 However, due to the absence of fans, very few instances were seen when there was significant air velocity around subjects and in most cases, the anemometer with a low resolution (0.1 m/s) returned zero reading showing the presence of still air condition. Nicol and Humphreys 48 further states that even at still air condition, due to convection current and bodily movement, there could be some air velocity relative to the human body, and thus cannot be treated as zero.…”
Section: Methodsmentioning
confidence: 99%